The Economics of the Conservation of Crop Genetic Resources in Colombia: A Case Study for Five Specific Crops - Moreno, Rocío del Pilar (Springer Nature, 2025)
Colombia is one of the countries with the most biological diversity in the world. Comprising only 0.7% of the continental area, Colombia has nearly 10% of the world's biodiversity. For this reason, Colombia is within the group of countries called "megadiversive countries." The great diversity of ecosystems in Colombia has been attributed to factors such as its localization between the two tropics and the great variety of altitudes, soils and climates that have formed many and different geographical zones. Local communities have used the biodiversity in Colombia for many years, and it has been a direct and indirect base for several productive activities. For this reason, the biological diversity plays an important role in national development and, in the future, will playa role in the options for sustainable development (Ministry of Environment, 1997).